Novel, selective EPO receptor ligands lacking erythropoietic activity reduce infarct size in acute myocardial infarction in rats. (November 2016) - Kiss, Krisztina; Csonka, Csaba; Pálóczi, János; Pipis, Judit; Görbe, Anikó; Kocsis, Gabriella F.; Murlasits, Zsolt; Sárközy, Márta; Szűcs, Gergő; Holmes, Christopher P.; Pan, Yijun; Bhandari, Ashok; et al.
Graphical abstract: Abstract: Erythropoietin (EPO) has been shown to protect the heart against acute myocardial infarction in pre-clinical studies, however, EPO failed to reduce infarct size in clinical trials and showed significant safety problems. Here, we investigated cardioprotective effects of two selective non-erythropoietic EPO receptor ligand dimeric peptides (AF41676 and AF43136) lacking erythropoietic activity, EPO, and the prolonged half-life EPO analogue, darbepoetin in acute myocardial infarction (AMI) in rats. In a pilot study, EPO at 100 U/mL significantly decreased cell death compared to vehicle (33.8 ± 2.3% vs. 40.3 ± 1.5%, p < 0.05) in rat neonatal cardiomyocytes subjected to simulated ischemia/reperfusion. In further studies (studies 1–4), in vivo AMI was induced by 30 min coronary occlusion and 120 min reperfusion in male Wistar rats. Test compounds and positive controls for model validation (B-type natriuretic peptide, BNP or cyclosporine A, CsA) were administered iv. before the onset of reperfusion. Infarct size (IS) was measured by standard TTC staining. In study 1, 5000 U/kg EPO reduced infarct size significantly compared to vehicle (45.3 ± 4.8% vs. 59.8 ± 4.5%, p < 0.05). In study 2, darbepoetin showed a U-shaped dose-response curve with maximal infarct size-reducing effect at 5 μg/kg compared to the vehicle (44.4 ± 5.7% vs. 65.9 ± 2.7%, p < 0.01). In study 3, AF41676 showed a U-shaped dose-response curve, where 3 mg/kg was the most effective dose compared to the vehicle (24.1 ± 3.9% vs. 44.3 ± 2.5%, p < 0.001). The positive control BNP significantly decreased infarct size in studies 1–3 by approximately 35%. In study 4, AF43136 at 10 mg/kg decreased infarct size, similarly to the positive control CsA compared to the appropriate vehicle (39.4 ± 5.9% vs. 58.1 ± 5.4% and 45.9 ± 2.4% vs. 63.8 ± 4.1%, p < 0.05, respectively). This is the first demonstration that selective, non-erythropoietic EPO receptor ligand dimeric peptides AF41676 and AF43136 administered before reperfusion are able to reduce infarct size in a rat model of AMI. Therefore, non-erythropoietic EPO receptor peptide ligands may be promising cardioprotective agents.